Seroprevalence of anti-HAV total antibodies among workers in wastewater treatment plants - Toseva, Elka; Atanasova, Mariya; Turnovska, Tanya (International journal of occupational medicine and environmental health, 2018)
Data on high frequency of hepatitis A virus (HAV) antibodies for wastewater treatment staff is contradictory. Literature lacks data on the seroprevalence of antibodies to HAV (anti-HAV) among workers in wastewater treatment plants (WWTPs) in Bulgaria. The aim of this study is to establish a specific humoral immune response to hepatitis A virus - anti-HAV total antibodies among staff in WWTPs. A complex study of health and working conditions included 110 subjects working in 3 WWTPs in Bulgaria (74% of all workers in the 3 studied WWTPs and 20% of all employees in Bulgaria registered in 2014 under the wastewater collection, discharge and treatment code of economic activity). Workers had been differentiated in 3 groups on the basis of their occupational work: operators, support staff and other workers exposed to biological agents. Venous blood from all 110 subjects was tested once for carriers of HAV antibodies. Anti-HAV total antibodies were found for 52.7% of workers in WWTPs. There is a positive association between activity performed in WWTPs (operators, maintenance personnel and others exposed) and a positive one for the presence of anti-HAV (Chi = 6.882, df = 2, p = 0.032). Odds ratio (OR) for hepatitis A increases 2.9 times in the group of operators vs. others exposed to biological agents in WWTPs (OR = 2.914, 95% confidence interval (CI): 1.149-7.393, Fisher's p = 0.039). Odds ratio for hepatitis A increases 4.3 times in the group of support staff from WWTPs vs. others exposed to biological agents in WWTP (OR = 4.295, 95% CI: 1.075-17.167, Fisher's p = 0.049). Higher frequency of anti-HAV antibodies among operators and maintenance personnel at WWTPs has been established as compared to other workers exposed to biological agents in WWTPs. There is a positive association between increasing age of the workers and the presence of anti-HAV. Int J Occup Med Environ Health 2018;31(3):307-315.